Assessing economic and environmental performance of multi-energy sharing communities considering different carbon emission responsibilities under carbon tax policy. (15th December 2021) - Li, Longxi; Zhang, Sen; Cao, Xilin; Zhang, Yuqing
Abstract: Excessive carbon emissions pose a significant threat to the sustainable development of society and have an irreversible impact on climate change. Local energy trading in low-carbon communities and the implementation of carbon tax policy are considered effective means to improve energy efficiency and reduce carbon emissions. In this regard, this paper proposes a multi-energy sharing mechanism based on Nash bargaining theory among communities with distributed energy systems. The impact of heterogeneous carbon emission responsibilities, including production responsibility, consumption responsibility, and shared responsibility, on the economic and environmental benefits of shared communities is explored under a carbon tax policy. The distributed solution of the multi-energy sharing problem is carried out through the alternating direction method of multipliers algorithm, which protects the privacy of stakeholders and maximizes social welfare and the fair allocation of shared benefits. Additionally, sensitivity analyses of electric and thermal coupling loads, carbon emission accounting coefficients, and carbon taxes, are conducted to provide further insights into the optimal schedule of distributed energy systems and the economic and environmental performance of community clusters. The method proposed in this paper can effectively address the problem of multi-energy sharing in the interconnected communities and reasonably determine the carbon emission responsibility of each trading entity under the carbon tax policy. Numerical results show that, compared with the traditional no energy sharing scenario, the proposed sharing mechanism can achieve a maximum of 5.91% cost savings and 9.25% carbon emission reduction. In addition, under the production responsibility scheme, the communities show the best economic performance, while under the consumption responsibility scheme, the communities achieve excellent environmental benefit. Graphical abstract: Image 1 Highlights: A Nash bargaining based community P2P multi-energy sharing mechanism is proposed. Different carbon emission responsibilities are considered in the P2P sharing problem. Distributed solving ensures the autonomy and privacy of participants. The economic and environmental performance under different scenarios are compared.